Aarrass v. Spain. (2018) - Unknown
Abstract : Human rights — Torture — Right to a fair trial — Arbitrary deprivation of liberty — Extradition — Obligations under Article 7 of International Covenant on Civil and Political Rights, 1966 — Risk of torture and other cruel, inhuman or degrading treatment or punishment — Arbitrary detention — Double punishment — Prohibition of discrimination — State Party's non-compliance with request for interim measures — Whether State Party violating its obligations under Article 7 of Covenant — Effective remedy International tribunals — United Nations Human Rights Committee — Jurisdiction — Admissibility — Other procedures of international investigation — Whether failure to exhaust local remedies — United Nations Human Rights Committee